Preparation of covalently linked DNA-RNA hybrids and arabinocytidine containing DNA fragments. - de Vroom, E (1988)
It will be demonstrated that 5'-O-DMT-N-acyl-deoxyribonucleosides, 5'-O-Lev-2'-O-MTHP-N-acyl-ribonucleosides and, also, 2'-O-MTHP-N-acyl-ara-cytidine can be coupled, via the hydroxybenzotriazole phosphotriester approach, to afford two types of DNA-RNA hybrids as well as ara-C containing DNA-fragments. The final removal of acid-labile DMT and MTHP groups could be effected by 1 h treatment with 80% acetic acid of the otherwise unprotected DNA-RNA hybrids. The same acidic hydrolysis did not result in complete removal of the 2'-O-MTHP group from the ara-C unit. Complete deblocking was accomplished after an additional 2 h aqueous HC1 (0.01 M; pH 2.00) treatment.